Properties of cellulose hydrogel from kenaf core prepared via pre-cooled dissolving method - Hatika Kaco,; Sarani Zakaria,; Nur Fazlinda Razali,; Chin, Hua Chia; Lina Zhang, Zhang; Saad Mohamad Jani, (Universiti Kebangsaan Malaysia, 2014)
Hydrogels were produced from cellulose derived from kenaf core powder with weight average molecular weight of cellulose was 1.68 × 105 and was dissolved in NaOH/urea solvent at -13oC. To obtain the optimal dissolving parameters, different percentage of NaOH, urea and kenaf core cellulose was used to study the degree of dissolution and formation of hydrogel. From the results obtained, it was found that the ratio of 6% NaOH/4% urea and 2% cellulose produced a good hydrogel. UV-Vis spectroscopy and XRD analysis were performed to analyze the transparency and crystallinity index of the cellulose solution and hydrogel, respectively. It showed that the hydrogel with the highest degree of solubility gave highest transparency due to the reduction of cellulose crystallinity as a result of the dissolution process. XRD analysis results showed the crystallinity of cellulose from kenaf core decreased by 70% after dissolution and hydrogel formation. Samples with 4% urea possess highest water content of 73% and decreased with increasing urea content.